2016 Australian Communications Theory Workshop (AusCTW) 2016
DOI: 10.1109/ausctw.2016.7433654
|View full text |Cite
|
Sign up to set email alerts
|

Physical layer split for user selective uplink joint reception in SDN enabled cloud-RAN

Abstract: To meet quality of service requirements on the uplink of future cellular networks, we need to exploit intercell interference among users eligible for cooperation. Cloud Radio Access Network (C-RAN) architecture is particularly favorable to realize cooperation between users in neighboring cells, since signal detection is realized in the same processing unit. The novel technology of Software Defined Networking (SDN) increases the flexibility of network optimization and scalability of computational resources. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…We use multi-cell joint scheduling for interfering UEs, so they transmit on the same frequency resource and their signals can be detected in the BBU-pool with conventional MIMO detection on the signals received by two (or more) RRHs. By slightly increasing transmit power, the same error rate as in the interference-free case is reached by using two times less resources [12].…”
Section: Network and Protocols Design 1) Cooperative Signal Procesmentioning
confidence: 53%
“…We use multi-cell joint scheduling for interfering UEs, so they transmit on the same frequency resource and their signals can be detected in the BBU-pool with conventional MIMO detection on the signals received by two (or more) RRHs. By slightly increasing transmit power, the same error rate as in the interference-free case is reached by using two times less resources [12].…”
Section: Network and Protocols Design 1) Cooperative Signal Procesmentioning
confidence: 53%
“…Please note that some of the references for this section are placed here due to estimated locations of the split, where option 7-3 was found most suitable. [5], [12], [29], [30], [31], [32], [36], [37], [38], [44], [47], [48], [49], [86] Simulations: [53], [58], [61], [73], [75], [87], [88], [89] Practical experiments: [90] In this split the scrambling, modulation and layer mapper are included in the DU, this gives a significant lower bitrate on the fronthaul link, particularly because the signal is modulated. During the modulation the bitrate is reduced because several bits (depending on the modulation order) are assigned to each symbol.…”
Section: E Option 7-3: High Phymentioning
confidence: 99%
“…Compared to option 6, and using MWR fronthaul then a lower throughput perceived by users, is obtained using split 7-3. [87] investigates split option 7-3 as an enabler for CoMP, the simulations show that this split can greatly facilitate the implementation of UL CoMP.…”
Section: E Option 7-3: High Phymentioning
confidence: 99%
“…Extensive CRAN studies have demonstrated the advantages and challenges of conducting the LTE physical layer baseband processing in the BBU [23]- [29]. The high transmission bitrate requirements for transporting the time-domain I/Q samples produced by the baseband processing at the BBU to the RRU have spurred research on fronthaul transport strategies, see e.g., [30]- [32], and alternative function splits between BBU and RRU [8], [33]- [42]. Complementary to this extensive research, which has examined cellular wireless access in an isolated manner and typically considered abstract models for the fronthaul between BBU and RRU, we propose to unify cable and wireless access networks.…”
Section: Related Workmentioning
confidence: 99%